ANALYSIS OF DIFFERENCES BETWEEN BOYS ATTENDING A FOOTBALL SCHOOL AND THOS WHO DO NOT DO SPORT WITH SPECIFIC-MOTOR ABILITIES - Slavko Molnar; Miroslav Smajić; Stevo Popović; Bogdan Tomić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
The subject sample of 240 boys aged 7-14 was divided to two subsamples of 120 boys each (active participants of "ЯMR Vojvodina" football school since the age of 7, and boys involved in sports, who regularly attended classes of physical education at school). The sample was subjected to 11 tests for evaluation of specific-motor abilities. The purpose of this research was to determine whether there are or there are not any differences in specific- motor abilities of subjects of the same age depending whether they play any sport or not. Analysis of results processed by discriminative analysis showed that the boys who attended football school achieved much better results in tests for evaluation of specific motor abilities than the boys who did not. At the age of 7-8, the differences can be attributed to efficient selection rather than the program contents due to the fact that they are beginners, whereas at older ages, these differences, being even higher in boys doing sports, can be attributed to the effects of program contents in the football school.